PENGARUH PROFITABILITY, CAPITAL INTENSITY, DAN INVENTORY INTENSITY TERHADAP TAX AVOIDANCE - Dzakira Latifatunisa (2021)
This study is a quantitative study that aims to examine the effect of profitability, capital intensity, and inventory intensity on Tax Avoidance. This study takes companies listed in the non-cyclical consumer goods sector on the Indonesia Stock Exchange in 2015 - 2019. The sample selection technique used is the Purposive Sampling technique and obtains 250 research data. Hypothesis testing using Multiple Linear Regression Analysis with a significance level of 5%. The results obtained from this study are based on a partial test, profitability has a positive effect on tax avoidance, while capital intensity and inventory intensity each have no effect on tax avoidance.